Ethical leadership and innovative work behavior: The mediating role of individual attributes - Zulfiqar Ahmed Iqbal; Ghulam Abid; Francoise Contreras; Qandeel Hassan; Rabbia Zafar (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Based on the social exchange theory, the aim of this study is to investigate the direct and indirect influence of ethical leadership on employee innovative work behavior, examining the intervening role of individual variables such as thriving at work and attitudes towards performing well in this relationship. The data was collected using self-reporting survey questionnaires by using a multi-source and cross-sectional study design with service sector employees from two different samples: the U.K. and Pakistan. The findings supported the hypothesized model, where direct and dual mediation were tested. The results extend our understanding as to how positive attitude and psychological states together create positive feelings in employees and enhance their capacity for creative thinking and implementations of new ideas.
Keywords: 650; thriving at work; attitude towards performing well; employees individual attributes; ethical leadership; innovative work behavior